2020
DOI: 10.7461/jcen.2020.22.2.97
|View full text |Cite
|
Sign up to set email alerts
|

A safer endovascular technique for pre-operative embolization of juvenile nasopharyngeal angiofibroma: avoiding the pitfalls of external carotid artery – internal carotid artery anastomoses

Abstract: Intra-arterial embolization of juvenile nasopharyngeal angiofibroma (JNA) prior to surgical resection is the preferred approach to minimize blood loss during surgical resection of the tumor. However, the presence of external carotid artery–internal carotid artery (ECA-ICA) anastomoses may hinder complete tumor embolization due to the associated risk for embolic complications. Here, we evaluate the use of a balloon-assisted embolization (BAE) technique in the treatment of JNA. We conducted a retrospective revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Elhammady et al utilized the same ImageJ software to determine the percentage of devascularization describes a 77%-93% mean obliteration rate after endovascular treatment of 10 patients with Onyx, which is comparable to our results [16]. Rosenbaum-Halevi et al also describe a case series of nine patients that underwent pre-resection JNA embolizations with Onyx with a mean tumor volume embolization/devascularization of 84%, which is also similar to our results [19]. Thus, Onyx is shown to be an effective agent yielding high percentages of devascularization of tumors without a high risk of complications or neurological injury.…”
Section: The Extent Of Devascularization Of Jnassupporting
confidence: 90%
See 2 more Smart Citations
“…Elhammady et al utilized the same ImageJ software to determine the percentage of devascularization describes a 77%-93% mean obliteration rate after endovascular treatment of 10 patients with Onyx, which is comparable to our results [16]. Rosenbaum-Halevi et al also describe a case series of nine patients that underwent pre-resection JNA embolizations with Onyx with a mean tumor volume embolization/devascularization of 84%, which is also similar to our results [19]. Thus, Onyx is shown to be an effective agent yielding high percentages of devascularization of tumors without a high risk of complications or neurological injury.…”
Section: The Extent Of Devascularization Of Jnassupporting
confidence: 90%
“…Elhammady et al demonstrated that embolization of these tumors can be done efficiently with a direct puncture with a decreased fluoroscopy time, better tumor devascularization, and decreased estimated blood loss [16]. Rosenbaum-Halevi et al demonstrated efficient embolization of JNAs through dual access of both the ECA and the internal carotid artery (ICA) [19]. A 6F catheter was placed in the ECA with subsequent injection of Onyx 34 into the tumor vessel while a balloon catheter was inflated in the ICA to prevent inadvertent embolization of normal vessels and travel of embolic material into the intracranial circulation [19].…”
Section: Types Of Embolizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…During an initial diagnostic angiogram, JNAs that show external carotid-internal carotid anastomoses are recommended to be embolized by some modified techniques like using microcatheter, preferring liquid embolic agent over particulate agents, or adopting balloon-assisted embolization for the safety of the procedure. Otherwise, there is a risk of intracranial migration of particles resulting in serious neurological complications like stroke and vision loss [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative embolization is used for virtually all cases of JNA, resulting in reduction in intraoperative bleeding, occlusion of surgically inaccessible arterial feeding vessels, decreased operative time and improved surgical visualization, identification and protection of adjacent structures [4][5][6]. This results in a significant reduction in overall surgical complications and, despite some reports of safe resection without embolization, it is considered to be the standard of care in most centers [7][8][9]. In this study, we describe our single-center experience in preoperative JNA devascularization with the injection of polyvinyl alcohol (PVA) into major lesion feeders, highlighting the safety and efficacy of this technique.…”
Section: Introductionmentioning
confidence: 99%